The Effect of Probiotic Addition Frequency InCulture of Baung (Hemibagrus nemurus)in Peat Swamp Water Media With Biofloc Technology - Shafiq, Muhammad; Rusliadi, Rusliadi; Putra, Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRAKThis research was conducted from February to April 2019, at the Laboratory of Technical Services Unit Aquaculture of Technology, Faculty of Fisheries and Marine University of Riau. The purpose of this study was to determine the frequency of the addition of appropriate probiotics in culture of baung (Hemibagrus nemurus) on peat swamp water media with biofloc technology. This study used completely randomized design (CRD) of one factor consisting of five levels of treatment with three replications.  The treatments applied are (1) once every 5 days, (2) once every 10 days, (3) once every 15 days, (4) once every 20 days, (5) control with a dose of 10 ml/m3 This is able to increase the growth and survival of baung fish (Hemibagrus nemurus), namely by growth in absolute weight 4.12 g, absolute length 4.43 cm, specific growth rate 2.37% feed conversion ratio 0.89, survival rate 83.33%, volume flock 12.5 ml/l. Water quality parameters such as: temperature in all treatments ranged from 26-29 °C, pH ranged from 6.6-7, dissolved oxygen ranged from 5.7 to 6.0 mg/l, and ammonia ranged from 0.003 to 0.112 mg/l.Keywords: Probiotics, Biofloc, Growth, Survival, Baung Fish.